Subsurface Analysis Using Microtremor and Resistivity to Determine Soil Vulnerability and Discovery of New Local Fault - Adi Susilo; Alamsyah M. Juwono; Faridha Aprilia; Farizky Hisyam; Siti Rohmah; Muhammad Fathur Rouf Hasan (Civil Engineering Journal, 2023)
Microtremor and geoelectrical resistivity surveys have been conducted in areas where the April 10, 2021, earthquake of 6.1 Mw caused the most damage. Wirotaman Village, Malang Regency, was one of the regions with the most extensive damage. This study aims to investigate the seismic vulnerability and subsurface conditions that result in severe damage at the research location. This study's Horizontal to Vertical Spectral Ratio Analysis (HVSR) curve was derived from the recorded microtremor signal in the frequency domain. The frequency parameter and amplification factor obtained from the curve are used to determine the seismic vulnerability index. In addition, a geoelectrical resistivity study with a dipole-dipole configuration was conducted at the site with the most extensive damage. The results of this study show the correlation between the results of the HVSR curve analysis and geoelectrical resistivity in determining the seismic vulnerability of an area. The results indicated that the high seismic vulnerability index value ranged from Kg= 12.0 to 18.0, with the most severe damage concentrated in the Southwest at SA 05 and SA 06. Based on the results of the geoelectrical survey, information was obtained that several points of damage to buildings at SA 05 (red circle) were on the same line, where this condition was associated with the possibility of new faults at that location. This microtremor and geoelectric resistivity investigation reveals thick sedimentary deposits with a high seismic vulnerability index and low resistivity. This study's findings can be utilized as a guide for micro zonation studies in research areas. This research contributes to the surrounding community in the form of disaster mitigation, where construction must avoid local fault positions that have been found to reduce the level of damage when natural geological disasters occur.Â Doi: 10.28991/CEJ-2023-09-09-014 Full Text: PDF